Activity-Tuning of Supported Co–Ni Nanocatalysts via Composition and Morphology for Hydrogen Storage in MgH2 - Ding, Xiaoli; Ding, Hongfei; Song, Yun; Xiang, Cuili; Li, Yongtao; Zhang, Qingan (Frontiers in Chemistry, 2020)
Achieving cheap metal nanocatalysts with controllable catalytic activity is one of the critical challenges for improving hydrogen storage in Magnesium (Mg). Here, the activity of graphene-anchored Co‒Ni nanocatalysts can be regulated effectively by tuning of composition and morphology, which would result in significantly improved hydrogen storage in Mg. The catalytic activity of supported Co‒Ni nanocatalysts is demonstrated to be highly depend on the morphology and composition. When Ni was partly substitued by Co element, the shape of these nanocatalysts was shifted from spheres to plates, thus corresponding to decrease of their activity. These alterations intrinsically result in enhanced hydrogen storage properties of MgH2, i.e., not only exhibiting a decreased peak desorption temperature, but also positively changing the initial activation for sorption. These results obtained provide a deep understanding of the catalytic activation tuned by composition and morphology and further provide insights into improving hydrogen storage in Mg-based materials.